Effect of intratracheal dexmedetomidine administration on recovery from general anaesthesia after gynaecological laparoscopic surgery: a randomised double-blinded study. Issue 4 (10th April 2018) - Wang, Fei; Zhong, Haoxiang; Xie, Xiaoyan; Sha, Weiping; Li, Caili; Li, Zhenping; Huang, Zhuomei; Chen, Chaojin
Abstract : Objectives: To examine the efficacy of intratracheal dexmedetomidine (Dex) injection for the prevention of the laryngeal response on emergence from general anaesthesia following gynaecological laparoscopic surgery. Design: Prospective, randomised, double-blinded, controlled trial. Setting: A general hospital, Guangdong Province, China. Participants: All patients who underwent elective laparoscopic gynaecological surgery, aged 18–60 years old, 40–80 kg in weight, American Society of Anesthesiologists class I–II were eligible. Patients were excluded if they had respiratory disease, heart disorders which might represent risk factors of potential complications of Dex such as bradycardia, heart block, coronary heart disease, uncontrolled hypertension or the long-term use of sedative drugs. Intervention: Patients were randomly allocated to either receive intratracheal Dex (DT), intravenous Dex (DV) or intravenous saline (CON, n=30, respectively). In the DT and DV groups, Dex (0.5 µg/kg) was diluted and mixed in 1 or 20 mL of saline, respectively, and injected via the intratracheal or intravenous route 30 min before the completion of the surgery. Outcome measures: The primary outcome was the coughing extent among the three groups. Secondary outcomes included awareness time, extubation time, postoperative visual analogue scale and Steward recovery score. Results: Compared with the CON group, the extent of coughing was significantly reduced in both the DV group and the DT group. Furthermore, the mean time to awareness (13.4 (4.3) vs 8.8 (2.9), p<0.001) and the extubation time (14.3 (4.3) vs 8.4 (3.6), p<0.001) were reduced in the DT group. Patients in the DT group also experienced better early recovery quality and less pain than those in the CON group. Furthermore, intratracheal Dex administration contributed to improved stability in haemodynamics with no significant side effects. Conclusions: Intratracheal Dex administration may avoid untoward laryngeal responses for patients emerging from general anaesthesia after gynaecological laparoscopy. Trial registration number: ChiCTR-IOR-15007611.